Comparison of elite athletes` sexual violence experiences in and outside sport - Ohlert, J.; Rau, T.; Rulofs, B.; Allroggen, M. (German Journal of Exercise and Sport Research, 2020)
Background Research on the prevalence of sexual violence in sport mostly focuses on incidents of sexual violence that happen in the context of sport, but few studies are available that systematically target the lifetime prevalence of sexual violence in the athletes (as persons), combining experiences in sport and outside the sport system. The aim of the current study was thus to compare sexual violence experiences of elite athletes in Germany in sport with those outside sport.